Penerapan Desain Lambung Berbasis Variasi Sudut Deadrise untuk Meningkatkan Efisiensi Perahu Wisata Skala Kecil di Waduk Lecari - Syahputri, Viony Fako; Nugroho, Hendy Pambudi; Sihombing, Herawaty Magdalena; Fadhilah, Mahesa Arma; Anam, Khoirul; Abadi, Galang Wahyu; Raharja, Achmad Mukti (Universitas Tribhuwana Tunggadewi Malang, 2025)
Lecari Reservoir in Wringinagung Village, Gambiran, Banyuwangi, is a new natural tourism destination resulting from a community initiative that has successfully transformed a slum area into a clean and comfortable tourist area. Although the number of visitors is relatively high, especially on weekends, tourism development still faces obstacles such as the lack of variety of water rides, so visitors easily get bored. The solution offered is the design of a two-person tourist boat, with attention to good maneuverability so that it can operate optimally in the relatively narrow reservoir (area 1,829 m², depth 7 meters, width ± 25 meters). Maneuverability analysis is the primary focus because it affects the safety and comfort of boat operations. As part of the community service activities, research was also conducted to evaluate the effect of variations in the deadrise angle of the boat's hull on the Curve of Sectional Area (CSA) and boat resistance performance through numerical simulations. Five deadrise angle configurations (13°, 15°, 17°, 19°, and 21°) were tested at a speed of 15 knots. The results show that a 21° deadrise angle produces the lowest total resistance of 0.66 kN, thus recommending its application in the design of tourist boats in Lecari Reservoir. The results of this community service contribute to the design of a more efficient and environmentally friendly small-scale tourist boat hull to support the development of local tourism based on natural potential.ABSTRAKWaduk Lecari di Desa Wringinagung, Gambiran, Banyuwangi, merupakan destinasi wisata alam baru hasil inisiatif warga yang berhasil mengubah kawasan kumuh menjadi area wisata yang bersih dan nyaman. Meski jumlah pengunjung cukup tinggi, khususnya pada akhir pekan, pengembangan wisata masih menghadapi kendala pada kurangnya variasi wahana air, sehingga pengunjung mudah merasa bosan. Solusi yang ditawarkan adalah perancangan perahu wisata berkapasitas dua orang, dengan memperhatikan kemampuan manuver yang baik agar dapat beroperasi optimal di waduk yang relatif sempit (luas 1.829 m², kedalaman 7 meter, lebar ±25 meter). Analisis manuver menjadi fokus utama karena mempengaruhi keselamatan dan kenyamanan operasional perahu. Sebagai bagian dari kegiatan pengabdian, dilakukan juga penelitian untuk mengevaluasi pengaruh variasi sudut deadrise lambung perahu terhadap Curve of Sectional Area (CSA) dan kinerja tahanan perahu melalui simulasi numerik. Lima konfigurasi sudut deadrise (13°, 15°, 17°, 19°, dan 21°) diuji pada kecepatan 15 knot. Hasil menunjukkan bahwa sudut deadrise 21° menghasilkan tahanan total terendah sebesar 0,66 kN, sehingga direkomendasikan untuk diterapkan pada desain perahu wisata di Waduk Lecari. Hasil dari pengabdian masyarakat ini yaitu memberikan kontribusi dalam perancangan lambung perahu wisata skala kecil yang lebih efisien dan ramah lingkungan untuk mendukung pengembangan wisata lokal berbasis potensi alam